PERAN LITERASI KEUANGAN DALAM MEMEDIASI PENGARUH DISTRIBUSI PRODUKTIF ZAKAT TERHADAP PERILAKU EKONOMI MUSTAHIK PADA LAZ SIDOGIRI - Muhammad Noval Amirudin; Muhammad Nizar; Alimatul Farida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of productive zakat distribution on the economic behavior of mustahik through financial literacy as a mediating variable among productive zakat beneficiaries of LAZ Sidogiri. The study employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 50 productive zakat beneficiaries selected using purposive sampling techniques. Data analysis was conducted using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the assistance of SmartPLS 4 software. The results indicate that productive zakat distribution has a positive and significant effect on financial literacy and productive behavior of mustahik. However, productive zakat distribution does not have a significant effect on consumptive behavior. The findings also reveal that financial literacy significantly influences the economic behavior of mustahik and mediates the relationship between productive zakat distribution and both productive and consumptive behavior. These results suggest that the success of productive zakat programs depends not only on the amount of assistance provided but also on the beneficiaries’ ability to manage and utilize funds effectively. Therefore, productive zakat programs should be accompanied by continuous financial literacy education and business assistance to enhance the effectiveness of economic empowerment initiatives. This study contributes to the development of Islamic economics literature, particularly regarding the role of productive zakat and financial literacy in shaping the economic behavior of mustahik.